Plan de Promoción y Ventas para captar y retener clientes en el local de productos lácteos Ecualac “Zuú … Leche” del cantón Buena Fe - Hallo Ortíz, Franklin Gustavo. (2014)
The thesis called "Plan for Promotion and Sales to capture and retain customers in the dairy products store Ecualac" Zuu...Leche" at Buena Fe City" was conducted with the aim of improving sales results retrieved in the previous years, taking advantage of being a brand nationally recognized. Taking advantage that one of the strengths of the brand "Zuu..." Milk" is to have national presence, this research carried out an analysis, through surveys, of the level of acceptance in Buena Fe City of each of the products marketed nationally: milk, cheese and yogurt. It also delved into the internal and external analysis of the store to strengthen its positive points and improve its weaknesses. The types of research utilized were: i) bibliographic research that allowed the revision of textbooks specialized in the subject, and ii) field work that was carried out between current final consumers, potential final consumers and potential points of sale. This information was used to design a proposal which consists of a Plan for Promotion and Sales with the objective of increasing the sales of products "Zuu...Leche " in Buena Fe City through strategies and action plans.